High oil absorbable superhydrophobic melamine sponges and evaluation in oil spill clean‐ups. Issue 42 (21st April 2020) - Shui, Yonggang; Xian, Yupei; Chen, Lichao; Li, Meimei; Yao, Yongyi; Zhang, Qiyi
Abstract: Facing the environmental crisis to leakage of oil spills and chemicals, multifunctional absorbent with high oil absorption and selectivity urgently need to solve this matter. In our work, a high oil sorbent was designed and favorably fabricated by two simple immersions using melamine sponge as pristine and a series of oils were used to evaluate the oil absorption performances of the absorbent. Two immersions include adhesion of dopamine and grafting of the long chain hydrophobic agent. The prepared material is superhydrophobic with water contact angle is 165.9° ± 2.17 and high oil absorption to chloroform is 174 times by own weight, other oils are close to or over 100 times, but to water is only 0.5 times. The reusability reveals that the average recovery can keep more than 95% after 20 cycles. These advantages make it really potential to use in oil spill clean. Abstract :